أثر مهارة الاسترخاء العضلي على الخفض من الاحتراق النفسي للاعبي كرة السلة - دراسة تجريبية على فريق J Rbc بالشلف القسم الوطني الأول - - بن غالية محمد; بلعروسي سليمان; قندوز الغول خليفة (Journal of Sport Science Technology and Physical Activities, 2020)
The study aimed to show the effect of the muscle relaxation skill on reducing psychological burnout for basketball players. The researcher used the experimental method. The sample consisted of 15 male basketball players, was selected in the intended way, and the psychological combustion scale was applied as a study tool. The study concluded that there are differences Statistically significant between the mean scores of the same group in the pre and post measurement in the dimensions of the scale (emotional stress, physical stress, feelings of dullness) and that the application of the muscle relaxation skill has a significant impact in reducing the degrees of psychological combustion of basketball players during training.